Theoretical Principles Of Implementation Of The Idea Of Mentally And Physically Perfect In General Secondary Schools - Shadiyev Azizjon Yakubjonovich (Euro Asian Journal Publishing, 2023)
This article contains information about the content and essence of the role of aesthetic culture in the development of the reader’s personality.
Keywords: educational; creative; developmental